2017
DOI: 10.1186/s12885-016-3012-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of lactate dehydrogenase in advanced pancreatic ductal adenocarcinoma patients

Abstract: BackgroundThe prognostic role of pretreatment serum lactate dehydronegase (LDH) has been well established in many malignant tumors, albeit it remains under-discussed in pancreatic cancer. In the present study, we aimed to assess the association between baseline LDH levels and overall survival (OS) in advanced pancreatic ductal adenocarcinoma (PDAC) patients who did and did not receive subsequent chemotherapy.MethodsIn total, 135 retrospectively determined patients with locally advanced or metastatic PDAC, who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…On the other hand, there is evidence favoring that the inverse association between high pretreatment serum LDH level and poor OS may reflect heavy tumor burden or tumor aggressiveness. [5,6] Therefore, dynamically monitoring changes of post-therapy serum LDH level may also help to predict the therapeutic response and prognosis in patients with pancreatic cancer. For instance, a study by Xiao et al [46] found that postoperative high serum LDH was significantly correlated with worse OS in patients with early-stage PC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, there is evidence favoring that the inverse association between high pretreatment serum LDH level and poor OS may reflect heavy tumor burden or tumor aggressiveness. [5,6] Therefore, dynamically monitoring changes of post-therapy serum LDH level may also help to predict the therapeutic response and prognosis in patients with pancreatic cancer. For instance, a study by Xiao et al [46] found that postoperative high serum LDH was significantly correlated with worse OS in patients with early-stage PC.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate dehydrogenase (LDH)—a common serum enzyme—participates in the conversion of pyruvate into lactate, and plays a critical role in maintaining the continued glycolysis, which is closely associated with tumor initiation and progression. [57] It has been considered that LDH may act as an indicator for tumor burden and aggressiveness because it is required for tumor maintenance. [5,6] Moreover, there is evidence supporting that serum LDH levels increased in many cancers and was associated with prognosis of various cancer patients, including PC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LDH is the enzyme converting pyruvate to lactate in anaerobic conditions, and as PDAC is a poorly vascularized cancer type, hypoxia plays an important role in its progression. Serum LDH levels have been reported to be associated with PDAC prognosis and response to treatment [ 22 , 23 , 24 ], and the relation between NLR and LDH is another interesting area for future research.…”
Section: Discussionmentioning
confidence: 99%
“…LDHA is predominantly expressed in muscle tissue and at low levels in other tissues. High LDHA expression has been reported in a number of malignancies, including pancreatic cancer, and has been associated with tumor development, invasion, and metastasis [21,22,23]. Targeting of LDHA with siRNA or small molecule inhibitors has been reported to increase oxygen consumption and reactive oxygen species production, reduce glucose uptake and lactate production, and decrease tumor cell growth [21,24,25,26].…”
Section: Introductionmentioning
confidence: 99%